2014
DOI: 10.1016/j.ejps.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro porcine blood–brain barrier model for permeability studies: pCEL-X software pKaFLUX method for aqueous boundary layer correction and detailed data analysis

Abstract: In vitro blood-brain barrier (BBB) models from primary brain endothelial cells can closely resemble the in vivo BBB, offering valuable models to assay BBB functions and to screen potential central nervous system drugs. We have recently developed an in vitro BBB model using primary porcine brain endothelial cells. The model shows expression of tight junction proteins and high transendothelial electrical resistance, evidence for a restrictive paracellular pathway. Validation studies using small drug-like compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 64 publications
1
32
0
1
Order By: Relevance
“…In in vitro tests, caffeine, a more hydrophilic compound, was shown to permeate almost as fast as diazepam, a lipophilic compound often used as a fast-migrating transcellular marker that does not interact with efflux transporters (Zhao and Pollack, 2009, Mealey et al., 2010). On the contrary, in vivo data revealed that caffeine was significantly slower than diazepam, probably due to interactions with active transporters (Nakazono et al., 1992, Yusof et al., 2014). These in vivo observations were also reflected in our models.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro tests, caffeine, a more hydrophilic compound, was shown to permeate almost as fast as diazepam, a lipophilic compound often used as a fast-migrating transcellular marker that does not interact with efflux transporters (Zhao and Pollack, 2009, Mealey et al., 2010). On the contrary, in vivo data revealed that caffeine was significantly slower than diazepam, probably due to interactions with active transporters (Nakazono et al., 1992, Yusof et al., 2014). These in vivo observations were also reflected in our models.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 For instance, Wang et al used CDs as a drug delivery system for doxorubicin (DOX), which produced a pH-controlled DOX release. 14 Recently, an in vitro study demonstrated that CDs can potently inhibit insulin fibrillation, which is associated with neurological diseases.…”
mentioning
confidence: 99%
“…Åùå îäíèì èç ñïîñîáîâ èçó÷åíèÿ ïà-òîãåíåçà çàáîëåâàíèé ÖÍÑ è ïàòîëîãèè ÃÝÁ ÿâëÿåòñÿ èñïîëüçîâàíèå êëåòî÷íûõ ìîäåëåé ÃÝÁ in vitro [84]. Ïåðâîå ïîêîëåíèå aeèçíåñïîñîáíûõ êëåòî÷íûõ ìîäå-ëåé in vitro ïîÿâèëîñü îêîëî 30 ëåò íàçàä [61].…”
Section: ìîäåëè âîñïàëåíèÿ In Vivo è ìîäåëè ãýá âîñïðîèçâîäÿùèå êëåòunclassified